Perencanaan Heater Pada Proses Pembuatan Seng Di PT. KALIMANTAN STEEL CO. LTD - .,, Fuazen (ELKHA : Jurnal Teknik Elektro, 2013)
Abstract One type of heat exchanger used is the type of heat exchanger Shell and Tube. Feasibility of making use of a heat exchanger is heating fluid and the fluid is heated, how much economic value is obtained. From these data, the process of making zinc plate in the PT. Kalimantan Steel CO. LTD uses diesel as fuel for heating water H2SO4 + 1.5% with an average in the 30 liter to 2000 sheets of tin plate. Through the concept of the Energy Management Program (PME) heat exchanger made ??by utilizing the residual heat of backling as a substitute for diesel fuel. Keywords- Heat exchangers, shell and tube, the Energy Management Program (PME)